Spatial Analysis of Regional Vulnerability to Dengue Fever in Yogyakarta City - Purba, Maya; Feroza, Erisca (BKM Public Health and Community Medicine, 2024)
Purpose: This study was to conduct a spatial analysis of regional vulnerability to dengue hemorrhagic fever incidence in 14 districts of Yogyakarta City. Method: The method used was spatial geographic data analysis. Data on dengue incidence and potential risk factors were collected from the Yogyakarta City Health Office and the Central Bureau of Statistics, and GIS (Geographic Information System) techniques were integrated into Rstudio software to identify spatial patterns of dengue incidence and assess regional vulnerability. Results: Significant spatial patterns were observed in the distribution of DHF incidence in Yogyakarta City. Geographically close areas tend to have high Incidence Rate (IR) and Standardized Mortality Ratio (SMR) values, indicating incidence clusters. Mergangsan sub-district has the highest IR of 8 per 10,000 population with an SMR of 1.92, followed by Umbulharjo sub-district located east of Mergangsan with an IR of 6 per 10,000 population with an SMR of 1.33, and Mantrijeron and Kraton sub-districts located west of Mergangsan with an IR of 5 per 10,000 population and an SMR of 1.2. The analysis also revealed that males had a higher IR (24%) than females (19%), highlighting the difference in risk between these two groups. These differences include behaviors that influence the level of exposure to vectors, as well as possible biological differences in the response to dengue infection. Other factors, such as population density, vegetation density, vector susceptibility, and weather and sanitation conditions, also influence the incidence and spread of dengue cases in certain areas of Yogyakarta. Conclusion: Spatial analysis can be an effective tool to identify areas' vulnerability to DHF incidence. The findings show that there are clusters of incidence that require special attention in disease control and prevention efforts, especially in the Mergangsan area with the highest risk. Analysis of IR differences by gender showed that males are more susceptible to DHF than females. By understanding the spatial patterns and risk factors, public intervention strategies can be designed and implemented more effectively to reduce the burden of DHF in Yogyakarta City.